Pengaruh Pengetahuan dan Motivasi Kerja Terhadap Penerapan Early Warning Score System di RSUP H Adam Malik - Ita Pinem; Zulfendri - Zulfendri; Siti Saidah Nasution (Dian Nuswantoro Semarang, 2021)
ABSTRACTThe national and international scaled-accreditation in a hospital should implement Early Warning Score System (EWSS) as procedure to do early detection of any changing in condition which shows alarm, especially for patients. The data from RSUP H. Adam Malik Medan, revealed that of the 44 medical records, in the inpatiens wards, 46 % of them were are not accordance with the standardized. This research used cross sectional design which was aimed to analyze the influence of knowledge and work motivation on the implementation EWSS. The sample were 89 nurses who worked in the surgery department. The data were analyzed by using multiple linear regression analysis by applying the assumption of multicolliniarity, heteroscedasticity, and normality data. The result showed that the variables of knowledge and work motivation had positive influence on the implementation of EWSS (P-Value 0,00) which indicated that Y model = 0,236 X1+ 0,535 X2 in which Y was EWSS implementation, X1 was knowledge, and X2 was work motivation. The conclusion was that increase in knowledge and work motivation would be followed by the increase in EWSS implementation. It is recommended that the hospital management maximize the implementation of EWSS by increasing the level of knowledge and work motivation. Key Word: Knowledge, Work Motivation, EWSS